2020
DOI: 10.1177/2380084420969116
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions about Professional Dental Services during the COVID-19 Pandemic

Abstract: Background: Dental professionals are at high risk of being infected by and transmitting COVID-19 to patients. Patients’ perceived risk for infection and attitudes about receiving dental care during the pandemic are important to understand as patients consider returning to routine dental care as the pandemic progresses. Objective: The purpose of this study was to explore dental patients’ perceptions of susceptibility to contracting COVID-19, their related attitudes and beliefs regarding dental care visits, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 11 publications
(10 reference statements)
3
64
1
3
Order By: Relevance
“…On the other hand, the number of those who thought that other patients can transmit COVID-19 in the waiting area was more than those who thought otherwise. Similar to these results, Moffat et al reported that the greatest risk related to dental care in terms of COVID-19 was to contract the disease from other patients in the dental office (22). These data indicate that the precautions taken by dentists while treating patients instill confidence in patients.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, the number of those who thought that other patients can transmit COVID-19 in the waiting area was more than those who thought otherwise. Similar to these results, Moffat et al reported that the greatest risk related to dental care in terms of COVID-19 was to contract the disease from other patients in the dental office (22). These data indicate that the precautions taken by dentists while treating patients instill confidence in patients.…”
Section: Discussionsupporting
confidence: 59%
“…The reintroduction of scheduled activity in dental clinics due to the COVID-19 pandemic in the de-escalation phase should prioritise the safety of patients and professionals at the different stages of the care process, from patient selection and preparation to home care and clinical circuit organisation [37]. Among the preventive measures adopted by patients, the results of this study on Spanish dental hygienists coincide with the measures assessed in other previous studies (e.g., [25]), such as hand washing with hydroalcoholic gels, mouthwash rinsing prior to treatment, or spacing of appointments to avoid saturation in waiting rooms [27].…”
Section: Discussionmentioning
confidence: 99%
“…According to the data presented from the Spanish hygienists survey, appointment time management is the main measure taken in the oral health units of the public health service. According to Moffat et al in their study on the identification of patients' perceptions of risk susceptibility and attitudes towards COVID-19 [37], professionals and public institutions should adopt additional information measures aimed at patients to address the conditions, events, and fears that influence the delay of their visits or the low demand for dental care in this context, in order to ensure the safe reopening of clinics and to regain patient confidence [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Peloso et al [52] recommended that dentists should use technology for patient counseling about appointments and treatment to decrease their anxiety. Finally, it is necessary to share consistent information about biosafety protocols during dental care to reduce fear and anxiety in patients [56].…”
Section: Dental Patient's Concern About Dental Treatment In the Context Of Covid-19 Pandemicmentioning
confidence: 99%
“…• Concerning patients, an important aspect is to inform them about the safety of dental office visits. Communication about biosafety is a crucial aspect of reducing fear and anxiety in patients [56]. It is also essential to minimize care time and reduce the intervals between patient appointments [19].…”
Section: Recommendations and Considerations To Improve Mental Healthmentioning
confidence: 99%